2022
DOI: 10.1093/erae/jbac001
|View full text |Cite
|
Sign up to set email alerts
|

Market power, markup volatility and the role of cooperatives in the food value chain: evidence from Italy

Abstract: Agricultural cooperatives are often promoted as a way to give farmers countervailing market power and greater income stability. This paper investigates to what extent cooperatives in food supply chains achieve these objectives. We estimate firm-level markups and markup volatility in the Italian fruits and vegetable (F&V) and dairy sectors at both the farming and processing stages for the period 2007–2014. We find mixed results: compared to non-cooperatives, F&V processor cooperatives have higher markup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 115 publications
0
8
0
Order By: Relevance
“…Using data of a dairy cooperative in Italy from 2011 to 2016, Trestini and Chinchio (2018) found that mutual fund helped its member farmers reduce their feed cost vulnerability and thus protect their income. Lee and Van Cayseele (2022) found that while fruit and vegetable processor cooperatives enjoyed higher markups than non-cooperative processors, there was no significant difference in markup volatility between cooperative processors and non-cooperative processors. Thus, the role of agricultural cooperatives in stabilizing farm income is a complex and multifaceted issue that require further research to gain better understanding of the issue.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Using data of a dairy cooperative in Italy from 2011 to 2016, Trestini and Chinchio (2018) found that mutual fund helped its member farmers reduce their feed cost vulnerability and thus protect their income. Lee and Van Cayseele (2022) found that while fruit and vegetable processor cooperatives enjoyed higher markups than non-cooperative processors, there was no significant difference in markup volatility between cooperative processors and non-cooperative processors. Thus, the role of agricultural cooperatives in stabilizing farm income is a complex and multifaceted issue that require further research to gain better understanding of the issue.…”
Section: Introductionmentioning
confidence: 82%
“…Second , the market power achieved by cooperatives may be used in part to buffer farming businesses from demand shocks in output markets. Cooperatives could commit to purchase relatively stable volumes of inputs at relatively stable prices, thus maintaining farmer revenues (Lee and Van Cayseele, 2022). Output marketing services are critical for farmers to access output market (Hellin et al ., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Such a methodology requires firm microdata and, therefore, has the same data limitations as structural models. Nevertheless, there are some notable applications in EU dairy processing ( Čechura et al [25]; Koppenberg and Hirsch [57]; and Lee and Van Cayseele [58].…”
Section: Structural Modelsmentioning
confidence: 99%
“…To our knowledge, no previous study of US food manufacturing productivity or markups has included non-Hicks-neutral productivity, particularly considering labour-augmenting technical 1 Melitz and Polanec (2015) explain how to describe this productivity in what they call 'dynamic OP decomposition of productivity'. 2 Analysis of production integrated with markups in food manufacturing was mainly addressed using the New Empirical Industrial Organisation (NEIO) approach (Bhuyan & Lopez, 1997;Lopez et al, 2002;Lopez et al, 2018;and Koppenberg & Hirsch, 2021;Lee & Van Cayseele, 2022; see Sexton &Lavoie, 2001, andKaiser &Suzuki, 2006 for a review of earlier NEIO studies).…”
Section: Introductionmentioning
confidence: 99%